Characteristics of historical precipitation for winter wheat cropping in the semi-arid and semi-humid area - Fang, Dan; Huang, Jingyao; Sun, Weiwei; Ullah, Najeeb; Jin, Suwen; Song, Youhong (Frontiers in Plant Science, 2023)
Winter wheat (Triticum aestivum L.) is one of major crops in the area along Huai river, China where it is a semi-arid and semi-humid region with sufficient precipitation for an entire season, but with uneven distribution within various growth stages. The instability of precipitation is an important factor in limiting wheat production potential under climate change. Therefore, it is essential to characterise the precipitation associated with different crop developmental stages. Based on climate data from 1999 to 2020 in six representative meteorological stations, we characterised the historical precipitation relating to seven key growth stages in winter wheat. There is no clear trend of interannual variation of precipitation for wheat season, with an average of precipitation of 414.4 ± 121.2 mm. In terms of the distribution of precipitation grade within a season, light rain was dominant. Continuous rain occurred frequently during the pre-winter seedling and overwintering stages. The critical period of water demand, such as jointing and booting, has less precipitation. The fluctuation range of precipitation in sowing, heading-filling and maturation stages is large, which means that there is flood and drought at times. In conclusion, these findings provide a foundation for instructing winter wheat cropping in confronting with waterlogging and drought risk due to uneven precipitation in ‘Yanhuai’ region, China.